Corak Hermeneutika Al-Quran dalam Tafsir al- Zamakhsyary - Badrul Munir Chair (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2022)
Hermeneutics is a study of understanding to interpret and reveal the hidden meaning of the text, symbols, and human actions. Hermeneutics is widely used as an approach in the realm of interpretation. This research will describe the hermeneutics of the Qur'an in Al-Kashshaf by al-Zamakhsyary. This research is a qualitative type of research by applying the literature study model. The results of this study indicate that the interpretation of the al-Kashshaf is a bi al-Ra'yi interpretation (the more dominant interpretation relies on reasoning). In terms of hermeneutics, the hermeneutics pattern of al-Zamakhsyary in the understanding of al-Kashshaf can be grouped as subjective hermeneutics by decomposition that, first: the use of sense in the al-Kashshaf is very dominant and gets a reasonably high portion; Second, the balaghah and grammatical aspect in the al-Kashshaf interpretation look very thick. In this case, the authenticity of the editorial and text words are caught carefully; Third, al-Zamakhsyary uses other texts such as the Hadith and Jahiliyyah poetry to strengthen or describe the interpretation. Keywords: Hermeneutics, al-Zamakhsyary, Tafsir bi al-Ra’yi, Tafseer al-Kashshaf.